Human resource management gaining a competitive advantage - Noe, Raymond A.; Noe, Raymond A. (New York, NY McGraw-Hill Education (Asia), 2005)
Human Resource Management: Gaining A Competitive Advantage by Noe/Hollenbeck/Gerhart/Wright is back with a new and improved 4th edition. In this new economy, effective human resource management is all the more necessary to gain true competitive advantage in the marketplace, as competitors strive to win the war for talent. Four challenges companies face are the global challenge, the challenge of meeting stakeholder needs, the high performance work practices challenge, and the challenge of competing in the new economy. The authors bring these challenges to life by highlighting real-world examples pertaining to these 4 issues and relating it to the concepts within the chapter. This best-selling McGraw-Hill Human Resource Management title provides students with the technical background needed to be a knowledgeable consumer of human resource (HR) products and services, to manage HR effectively, or to be a successful HR professional. While clearly strategic in nature, the text also emphasizes how managers can more effectively acquire, develop, compensate, and manage the internal and external environment that relates to the management of human resources.
Chapter 1. Human Resource Management: Gaining a Competitive Advantage

Part I: THE HUMAN RESOURCE ENVIRONMENT
Chapter 2. Strategic Human Resource Management
Chapter 3. The Legal Environment: Equal Employment Opportunity and Safety
Chapter 4. The Analysis and Design of Work

Part II: ACQUISITION AND PREPARATION OF HUMAN RESOURCES
Chapter 5. Human Resource Planning and Recruitment
Chapter 6. Selection and Placement
Chapter 7. Training

Part III: ASSESSMENT AND DEVELOPMENT OF HRM
Chapter 8. Performance Management
Chapter 9. Employee Development
Chapter 10. Employee Separation and Retention

Part IV: COMPENSATION OF HUMAN RESOURCE
Chapter 11. Pay Structure Decisions
Chapter 12. Recognizing Employee Contributions with Pay
Chapter 13. Employee Benefits

Part V: SPECIAL TOPICS IN HUMAN RESOURCE MANAGEMENT
Chapter 14. Collective Bargaining and Labor Relations
Chapter 15. Managing Human Resources Globally
Chapter 16. Strategically Managing the HR Function
International edition
Includes bibliographical references and indexes.
Keywords: Personnel management -- United States